Modulating the allergenicity and functional properties of peanut protein by covalent conjugation with polyphenols. (30th July 2023) - He, Weiyi; He, Kan; Liu, Xiaoyu; Ye, Liying; Lin, Xiao; Ma, Li; Yang, Pingchang; Wu, Xuli
Highlights: The allergenicity of PPE declines through covalent conjugation with polyphenols (EGCG and CA). Covalently conjugation with polyphenols enhances the digestibility of PPE. The functional properties of PPE improved after covalent conjugation with polyphenols. Abstract: Peanut protein is a common food allergen. Our previous study demonstrated that the allergenicity of Ara h1 declines after covalent conjugation with polyphenols in vitro ; however, how polyphenols affect the structure, function, and allergenicity of peanut protein extract (PPE) after covalent conjugating needs clarifying. Here, we assessed how the structure, function, and allergenicity of PPE changed after covalent conjugation with epigallocatechin-3-gallate (PPE-EGCG) and chlorogenic acid (PPE-CA). PPE covalently conjugated with EGCG and CA using the alkali treatment method. Multi-spectroscopy showed that the structure of PPE-EGCG/CA conjugate changed, becoming less folded. In contrast, the functional properties of PPE significantly improved. The allergenicity of PPE-EGCG/CA significantly declined in vitro and in vivo experiments. Our findings confirm that covalent conjugation of PPE with EGCG and CA reduces the allergenicity and improves the functional properties of PPE by changing the structure of the protein.